The Pioneers of Islamic Education: A Critical Look at the Khulafaurrasyidin Period - Umair Talib (SYAMIL: Journal of Islamic Education, 2022)
The existence of Islamic education has actually existed and started since the first revelation was revealed or to be precise when the Prophet Muhammad saw received an order from Allah to disseminate Islamic teachings, so what was done was clearly included in the education category. This type of research is library research. The approach used is the Islamic Education Science approach. The data collection method is through the documentation method, while the data analysis uses content analysis. The results of the study show that the pattern and system of Islamic education at that time can be classified as fully managed autonomously by the people in a democratic manner, and only when Umar alone did the government take over the education system at that time so that teacher salaries were regulated by the government by taking them to the baitul mall managed by government, if now it is said to be the minister of finance. The curriculum used during the khulafaurrasyidin era was spelled out as one unit, which was centered on the Qur'an and Hadith. This is due to purify what has been taught by the Prophet Muhammad. As for Islamic educational institutions during the khulafaurrasyidin, they were centered on mosques and kuttab. The mosque is used as a spiritual fortress, a meeting place, and an Islamic educational institution, as a place for congregational prayers, reading the Qur'an and so on, and other institutions that color the orders of the khulafaurrasyidin also establish a kuttab which is next to the mosque then the house of the friends or scholars at that time also in the markets. When the spread of Islam became wider, the khulafaurrasyidin did not forget to also establish educational institutions in the conquered areas so that they could be enjoyed by all people. The kuttab was built next to the mosque on purpose because there are many children who often attend the mosque and of course will pollute the mosque while studying, so the kuttab is a new alternative after the mosque.